LIBERALIZATION AND PRIVATIZATION AS AN ENGINE OF ECONOMIC GROWTH IN DEVELOPING COUNTRIES: THE CASE OF THE NIGERIAN TELECOMMUNICATIONS INDUSTRY - Familusi, Ajibola (2005)
Although telecommunications has long been recognized as an essential catalyst for growth, investments in telecommunications infrastructure has not been a central focus for most developing countries. This is primarily because until recently, telecommunications authorities were government owned agencies and were subject to standard government budget practices which meant that they had compete for budget allocation from the state along with other bureaucracies. As funds were not allocated exclusively according to economic criteria, the telecommunications industry generally experienced a gap in investments as the gains associated with telecommunications investments were underestimated or simply unknown. The reform of the public sector in most developing countries in recent years has facilitated an upsurge in investment in the telecommunications industry .This has brought about questions as to the role of the private sector in economic development and also in particular what effects telecoms investments can potentially have on economic growth. This study looked into these issues in the context of the Nigerian telecommunications industry and the conclusion reached from a review of the literature and the study findings reveal that: A positive relationship exists between economic development and infrastructure investments in general and telecommunications in particular. Sustained Investments in telecommunications on its own are not enough to ensure economic growth, but a lack of adequate telecommunications infrastructure and investment can significantly constrain economic development.